Virulence regulation of Zn2+ uptake system znuABC on mesophilic Aeromonas salmonicida SRW-OG1 - Wang, Jiajia; Xiu, Lijun; Qiao, Ying; Zhang, Youyu (Frontiers in Veterinary Science, 2023)
Psychrophilic Aeromonas salmonicida could not grow above 25°C and therefore thought unable to infect mammals and humans. In our previous study, a mesophilic A. salmonicida SRW-OG1 was isolated from Epinephelus coioides with furunculosis. Through the analysis of preliminary RNA-seq, it was found that the Zn2+ uptake related genes znuA, znuB and znuC might be involved in the virulence regulation of A. salmonicida SRW-OG1. Therefore, the purpose of this study was to explore the effect of znuABC silencing on the virulence regulation of A. salmonicida SRW-OG1. The results showed that the growth of the znuA-RNAi, znuB-RNAi, and znuC-RNAi strains was severely restricted under the Fe2+ starvation, but surprisingly there was no significant difference under the Zn2+ restriction. In the absence of Zn2+ and Fe2+, the expression level of znuABC was significantly increased. The motility, biofilm formation, adhesion and hemolysis of the znuA-RNAi, znuB-RNAi, and znuC-RNAi strains were significantly reduced. We also detected the expression of znuABC under different growth periods, temperatures, pH, as well as Cu2+ and Pb2+ stresses. The results showed that znuABC was significantly up-regulated in the logarithmic phase and the decline phase of A. salmonicida. Interestingly, the trend of expression levels of the znuABC at 18, 28, and 37°C was reversed to another Zn2+ uptake related gene zupT. Taken together, these indicated that the znuABC was necessary for A. salmonicida SRW-OG1 pathogenicity and environmental adaptability, and was cross regulated by iron starvation, but it was not irreplaceable for A. salmonicida SRW-OG1 Zn2+ uptake in the host.